2023
DOI: 10.3389/fphar.2023.1247664
|View full text |Cite
|
Sign up to set email alerts
|

Dipyridamole activates adenosine A2B receptor and AMPK/cAMP signaling and promotes myogenic differentiation of myoblastic C2C12 cells

Miguel Marco-Bonilla,
Raquel Herencia,
María Fresnadillo
et al.

Abstract: Introduction: Sarcopenia is defined as a loss of muscle mass and strength. ATP homeostasis is crucial during myogenesis. We determined how the purinergic system modulates myogenesis using dipyridamole (blocks adenosine taken up by the cells) and tenofovir (inhibits ATP release) in a myoblast cell line.Methods: C2C12 cells were differentiated in the presence/absence of tenofovir/dipyridamole, with/without the A2B selective inhibitor PSB-603. Extra-/intracellular nucleotides were examined via HPLC. The expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…This ratio activates AMPK via phosphorylation and allows for the restoration of ATP levels from AMP [125]. The activation of both PKA and AMPK has been observed to promote CREB expression [121,126,127]. CREB promotes the expression of genes involved in mitochondrial biogenesis (PGC-1 and TFAM) and muscle regeneration, preventing alterations in muscles [128,129] (Figure 2).…”
Section: Adenosine Receptors In Muscles and Fat And Their Role In Sar...mentioning
confidence: 99%
See 4 more Smart Citations
“…This ratio activates AMPK via phosphorylation and allows for the restoration of ATP levels from AMP [125]. The activation of both PKA and AMPK has been observed to promote CREB expression [121,126,127]. CREB promotes the expression of genes involved in mitochondrial biogenesis (PGC-1 and TFAM) and muscle regeneration, preventing alterations in muscles [128,129] (Figure 2).…”
Section: Adenosine Receptors In Muscles and Fat And Their Role In Sar...mentioning
confidence: 99%
“…Recently, it was reported that the pharmacological increase in extracellular adenosine by dipyridamole in the myoblastic line C3C12 leads to an increase in A2B adenosine receptor expression [127]. Subsequently, this leads to cAMP-PKA-CREB increase and AMPK activation [127].…”
Section: A2b Signaling Via Ampk/camp and Mitochondrial Adp Sensibilit...mentioning
confidence: 99%
See 3 more Smart Citations